Autoimmunity in atopic dermatitis: Biomarker or simply epiphenomenon?. Issue 7 (8th May 2014) - Cipriani, Francesca; Ricci, Giampaolo; Leoni, Maria Chiara; Capra, Lucetta; Baviera, Giuseppe; Longo, Giorgio; Maiello, Nunzia; Galli, Elena
Abstract The idea that a mechanism of autoimmunity could play a role in the pathogenesis of atopic dermatitis gained support from the observation that patients with atopic dermatitis display IgE reactivity to a variety of human protein antigens, several of which have been characterized at molecular level. A broad spectrum of at least 140 IgE‐binding self‐antigens associated with atopic dermatitis has been demonstrated; they might promote, perpetuate, or both, skin inflammation by binding IgE antibodies or activating specific T cells. Even if the presence of autoreactivity seems to be associated with the severity of the disease and may be used as a parameter reflecting chronic tissue damage, at the state of art the role of autoimmunity in atopic dermatitis is far from clear. Data from the literature show that the use of autoantibodies as biomarkers of atopic dermatitis are still limited by the evidence that the epiphenomenon of autoreactivity is detectable only in a percentage of patients and that the involved self‐allergens often are not the same; further longitudinal case‐control studies are needed to investigate and to clarify the pathogenethic role of autoimmunity in the course of atopic dermatitis.